Strength Analysis of Metro Kapsul Train's Upper Structure Using Finite Elemen Metho wth Shell Elemen Models - LUTFIA MASDUQI (NIM : 13113089), ALIF
Metro Kapsul is one of the national trains owned by PT. Teknik Rekayasa Kereta Kaspul. One of the stages in order Metro Kapsul could be launched in Indonesia is certification by the Government of Indonesia. One of the requirements of this certification to be performed is static testing for upper structure of Metro Kapsul. To evaluate strength of structures and to support statistical test requirement, it is needed fo Metro Kapsul structure to be analyzed. This final project has a purpose to analyze in order to evaluate strength of upper structure and to get location of strain gage-LVDT for statistical test.The Model which be analyzed is the model Metro Kapsul on 21 Juni 2017. Analysis of structure is using finite element method with shell element model. The structure is analyzed based on the load case applicable to Ministerial Regulation of Indonesia No. 175 Year 2015 and JIS E 7105. Methodology begins with studiying literatures, completion of information about model and specification of metro capsule, formulation of various cases of loading, discussion with team of certification, modeling finite element, so that obtaned analysis result for strength of structure and location of strain gage-LVDT. Based on the analysis results, the maximum stress of body frame occurs on the bracket of 303.4 MPa (σvm) in the case of torsional load test and 255.7 MPa (σ1) in the case of compression load test with passenger load. While the maximum stress of base frame is 770,8 MPa (σvm) and 864,5 MPa (σ1) in real case of vertical loading. The maximum stress of the base frame occurs at the suspension pedestal exceeding the strenghth yield of the material so that it will undergo plastic deformation.. Furthermore, also obtained the location of the installation of strain gage and LVDT for static test requirement.